RASUAH DALAM PERSPEKTIF HADITH: HUKUMAN DAN PENGUATKUASAAN - Mohamad Riza, Nurul Syahadah; Md Ariffin, Mohd Farhan; Harun, Muhammad Safwan (Jurnal ’Ulwan, 2023)
Misconduct of integrity is a major issue today. The practice of corruption is a stumbling block that opens the doors to damage and malpractice. Therefore, this study aims to discuss the concept, punishment, and enforcement of corruption from the perspective of the hadith. Using inductive, deductive, and thematic analysis methods, the study found that corruption is a cursed act in Islam, but there is no specific punishment stated in the hadith for corruption as it is categorised under the punishment of ta’zir. Malaysian law enshrines corruption under the Akta Suruhanjaya Pencegahan Rasuah 2009.